Effect of intranasal and intraperitoneal administration of peptides Semax and Noopept on the behavior of BALB/c mice - E. V. Vasilieva; R. M. Salimov; G. I. Kovalev (Фармакокинетика и Фармакодинамика)
Effects of intraperitoneal and intranasal administration of peptides noopept (1 mcg/kg/day for 5 days) and semax (0,6 mcg/ kg/day for 5 days), known to produce nootropic and anxiolytic actions were tested in BALB/c mice (the Line is characterized by Lowered exploratory efficacy and elevated anxiety) by the use closed exploratory cross maze. Both semax and noopept using both routes of administration produced nootropic and anti-anxiety activity. In case of intraperitoneal administration of both peptides the anti-anxiety effect was more prominent, while after intranasal treatment the elevation of exploratory behavior was better seen. The discrepancy between the mice behavior after different routes of the peptides can be attributed to differences in pharmacokinetics, biotransformation and dynamic anxiolytic and nootropic activity of the drugs.